The Public Speaking Communication Model of Visually Impaired Massage Therapists in Enhancing Customer Experience in Bandung - Rizki Surya Tawaqal; Ridlwan Muttaqin; Recky Recky (International Journal of Business, Management and Economics, 2026)
This study is motivated by the need to understand the communication models used by blind massage therapists in delivering their services, as communication plays a crucial role in shaping the customer experience. The research problem focuses on how these public speaking models are manifested and how they influence customer perceptions and satisfaction. A descriptive qualitative method was applied, involving direct observation at Rumah Bugar Sentra Wyata Guna and in-depth interviews with four blind massage therapists. The findings reveal four distinct public speaking communication models: Communicative-Relational, Silent-Reflective, Informative-Educative, and Humorous-Relaxed. Each model contributes differently to the customer experience, ranging from building trust, creating a calm atmosphere, providing additional knowledge, to fostering a cheerful and enjoyable environment. The study concludes that public speaking competence is not merely a complementary skill but a strategic added value that enhances customer satisfaction and strengthens the professional position of blind massage therapists within the health and relaxation service industry